2010
DOI: 10.1097/ijg.0b013e31819f9330
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase-like 1 Gene Polymorphisms in German Patients With Normal Tension Glaucoma, Pigmentary Glaucoma and Exfoliation Glaucoma

Abstract: Our study reveals that in the German population the LOXL1 genetic predisposition is limited to exfoliation glaucoma and does not include normal tension glaucoma. In addition, our study implicates that LOXL1 polymorphisms are not likely to have a major influence on the pathophysiology of pigmentary glaucoma. However, 1 nonsynonymous polymorphism may serve as a predictor of age at disease onset in pigmentary glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
4
23
0
1
Order By: Relevance
“…Targeting LysOXL2 with an inhibitory monoclonal antibody (AB0023) has been reported efficacious in both primary and metastatic xenograft models of cancer, as well as in liver and lung fibrosis models (Barry-Hamilton et al 2010) and also pro-BAPNs showed good levels of in vitro hypoxia-selective inhibition of LysOX activity (Carlotta et al 2009). The LysOXL1 genetic predisposition is limited to exfoliation glaucoma and does not include normal tension glaucoma (Wolf 2010).…”
Section: Dietary Copper and Lysox Productionmentioning
confidence: 99%
“…Targeting LysOXL2 with an inhibitory monoclonal antibody (AB0023) has been reported efficacious in both primary and metastatic xenograft models of cancer, as well as in liver and lung fibrosis models (Barry-Hamilton et al 2010) and also pro-BAPNs showed good levels of in vitro hypoxia-selective inhibition of LysOX activity (Carlotta et al 2009). The LysOXL1 genetic predisposition is limited to exfoliation glaucoma and does not include normal tension glaucoma (Wolf 2010).…”
Section: Dietary Copper and Lysox Productionmentioning
confidence: 99%
“…Following the removal of duplicate articles and the screening process, 79 full-text articles were assessed for eligibility. Among these, 37 studies met the inclusion criteria and were included in the meta-analysis (Thorleifsson et al, 2007;Fingert et al, 2007;Fan et al, 2008;Hewitt et al, 2008;Fuse et al, 2008;Ozaki et al, 2008;Mossböck et al, 2008;Challa et al, 2008;Pasutto et al, 2008;Schlötzer-Schrehardt et al, 2008;Aragon-Martin et al, 2008;Yang et al, 2008;Hayashi et al, 2008;Tanito et al, 2008;Mabuchi et al, 2008;Mori et al, 2008;Ramprasad et al, 2008;Lee et al, 2009;Chen et al, 2009;Lemmelä et al, 2009;Wolf et al, 2010;AbuAmero et al, 2010;Williams et al, 2010;Mayinu & Chen et al, 2011;Malukiewicz et al, 2011;Sagong et al, 2011;Abu-Amero et al, 2011;Rautenbach et al, 2011;Jaimes et al, 2012;Micheal et al, 2012;Chiras et al, 2013;Metaxaki et al, 2013;Kasım et al, 2013;Park et al, 2013;Anastasopoulos et al, 2014;Dubey et al, 2014;de Juan-Marcos et al, 2014). In two of these studies (Thorleifsson et al, 2007;…”
Section: Resultsmentioning
confidence: 99%
“…In the Galbraith plot ( Supplementary Fig. S34), nine studies were outside the 95% CI from the lnOR (Thorleifsson et al, 2007;Fan et al, 2008;Mossböck et al, 2008;Pasutto et al, 2008;Wolf et al, 2010;Chiras et al, 2013;Kasim et al, 2013), causing the heterogeneity in the results. In a sensitivity analysis excluding these nine studies, heterogeneity was not significant (I 2 = 20.8%, p = 0.239; Supplementary Fig.…”
Section: Between-study Heterogeneity Analysismentioning
confidence: 95%
“…Kurji et al discovered that inflammation-associated genes and immune response pathways were the predominant responses of RPE to oligomeric Aβ stimulation [42]. In the neovascular form of AMD, 196 X. Li et al Drusen may lead to CNV by reducing RPE adhesion to Bruch's membrane and allowing for vessels to enter the sub-RPE space.…”
Section: Pathology Of Inflammation In Amdmentioning
confidence: 99%
“…LOXL1 codes for an enzyme that is essential for the formation, maintenance, and remodeling of elastic fibers and prevents age-related loss of tissue elasticity. The association of LOXL1 with XFS has been confirmed in populations from throughout the world including Asian populations of Chinese, Indian, and Japanese [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205]. The association of LOXL1 with XFS has been confirmed in populations from throughout the world including Asian populations of Chinese, Indian, and Japanese [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205].…”
Section: Exfoliation Syndrome Glaucomamentioning
confidence: 99%